Yolk-shell type Co9S8 / ZnS / CN coated SiO2 catalyst as well as preparation and application of Yolk-shell type Co9S8 / ZnS / CN coated SiO2 catalyst

By developing the Yolk-shell type CO9S8/ZNS/CN@SiO2 catalyst in the field of electrolytic hydrogen, solve the problem of the existing non-valuable metal OEER catalysts in high potential and long-term operation conditions, and realize the lack of catalytic performance. Efficient, stable and low -cost electrocatalytic hydrogen production effects.

CN119372696APending Publication Date: 2025-01-28GUANGDONG UNIV OF EDUCATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411406059.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing non-precious metal oxidation and reaction (OER) catalysts such as transition metal sulfides have problems with insufficient stability and catalytic performance under high potential and long-term operating conditions, which limits their application in the field of electrolytic hydrogen production.

Method used

By using the metal organic framework (MOF) as the construction module, and the silicon is modified by the outer surface, the Yolk-SHELL type CO9S8/ZNS/CN@SiO2 catalyst is formed. This method uses the dual strategies of vulcanization and high -temperature heat solution to transform the transition metal vulcosion with the core of nitrogen doped carbon, and overseas the silicon dioxide shell layer to optimize the structural performance of the catalyst.

Benefits of technology

It significantly improves OER catalytic activity, enhances electrochemical performance, prolongs the service life of catalysts, and reduces production costs. It provides a highly efficient, clean and sustainable hydrogen catalytic hydrogen production path.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and discloses a Yolk-shell type Co9S8 / ZnS / CN (at) SiO2 catalyst as well as a preparation method and application of the Yolk-shell type Co9S8 / ZnS / CN (at) SiO2 catalyst. According to the invention, a metal organic framework (MOF) is used as a construction module, and an MOF coated SiO2 primary structure is formed by modifying silicon dioxide (SiO2) on the outer surface. And then, by adopting a dual strategy of vulcanization and high-temperature pyrolysis, successfully converting to obtain a high-performance catalyst of which the core is nitrogen-doped carbon-coated transition metal sulfide (Co9S8 / ZnS) and the outside is coated with a silicon dioxide shell layer. The preparation process is efficient and environment-friendly, and opens up a new path for developing an efficient electrocatalytic hydrogen production catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst and a preparation and application thereof. Background Art

[0002] As global energy demand continues to grow, the development of efficient, clean and sustainable energy technologies has become increasingly important. Hydrogen production by water electrolysis is a promising technology because it can produce high-purity hydrogen, which is considered to be one of the clean energy sources of the future. However, the oxygen evolution reaction (OER) in the water electrolysis process is a key step that limits its efficiency because it requires high overpotential and current density. Although traditional efficient OER catalysts such as precious metal oxides (RuO2 and IrO2) are highly active, their high cost and scarcity limit their large-scale applications. Therefore, the development of low-cost, efficient and stable non-precious metal OER catalysts has become a research hotspot.

[0003] Transition metal sulfides (TMSs) are considered to be promising candidates for non-precious metal OER catalysts due to their unique electronic structures and abundant surface active sites. Among them, cobalt sulfide (Co9S8) and zinc sulfide (ZnS) have attracted much attention due to their low cost, environmental friendliness, and high catalytic activity. However, TMSs still face some challenges in practical applications, such as relatively poor conductivity and instability under high potential and long-term operation conditions, which limit their catalytic efficiency and service life.

[0004] Therefore, it is particularly important to improve the stability and catalytic performance of single sulfide catalysts through component design and structural optimization of composite materials, and to explore a method that can effectively prepare non-precious metal-based catalysts with low cost, excellent catalytic effect and strong stability. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst.

[0006] The present invention cleverly uses metal organic framework (MOF) as a building block and modifies the outer surface with silicon dioxide (SiO2) to form a MOF@SiO2 primary structure. Subsequently, a dual strategy of sulfurization and high-temperature pyrolysis is adopted to successfully transform a high-performance catalyst with a core of nitrogen-doped carbon-wrapped transition metal sulfide (Co9S8 / ZnS) and a silicon dioxide shell. This preparation process is not only efficient but also environmentally friendly, opening up a new path for the development of efficient electrocatalytic hydrogen production catalysts.

[0007] Another object of the present invention is to provide a Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst prepared by the above method.

[0008] Another object of the present invention is to provide an application of the above-mentioned Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst in the field of hydrogen production by water electrolysis.

[0009] The purpose of the present invention is achieved through the following solutions: A method for preparing a Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst comprises the following steps: (1) mixing a cobalt salt solution and a 2-methylimidazole solution, allowing the mixture to react, separating, and drying a solid product to obtain ZIF-67; (2) dispersing ZIF-67 in a solvent, adding a zinc salt solution and a 2-methylimidazole solution, stirring the reaction, separating, and drying the solid product to obtain ZIF-67@ZIF-8; (3) Dispersing ZIF-67@ZIF-8 and 2-methylimidazole in a solvent respectively, mixing the two, adding hexadecyltrimethylammonium bromide (CTAB) solution, adding tetraethyl silicate (TEOS), stirring the reaction, separating, and drying to obtain ZIF-67@ZIF-8@SiO2; (4) ZIF-67@ZIF-8@SiO2, thioacetamide and solvent are uniformly mixed, subjected to sulfidation reaction, separated and dried to obtain a sulfidation product; the sulfidation product is calcined in an inert atmosphere, cooled and a Co9S8 / ZnS / CN@SiO2 catalyst is obtained.

[0010] The cobalt salt in step (1) is at least one of (CH3COO)2Co·6H2O, Co(NO3)2·6H2O, and CoCl2·6H2O.

[0011] In step (1), the concentration of the cobalt salt solution is 0.1-0.5 mol / L, and the concentration of the 2-methylimidazole solution is 0.2-4 mol / L.

[0012] The amounts of the cobalt salt solution and the 2-methylimidazole solution in step (1) are such that the molar ratio of cobalt ions to 2-methylimidazole in the mixed solution is 1:2-8.

[0013] The temperature of the static reaction in step (1) is room temperature and the time is 10-24 hours.

[0014] The zinc salt in step (2) is at least one of Zn(NO3)2·6H2O, Zn(CH3COO)2·2H2O, and ZnCl2.

[0015] In step (2), the dosage ratio of ZIF-67 to solvent is 50-200 mg:10-50 mL; the concentration of zinc salt solution is 20-40 mg / mL; and the concentration of 2-methylimidazole solution is 20-40 mg / mL.

[0016] The mass ratio of ZIF-67 to 2-methylimidazole in step (2) is 50-200:200-2000.

[0017] The amounts of the zinc salt solution and the 2-methylimidazole solution in step (2) are such that the molar ratio of zinc ions to 2-methylimidazole in the mixed solution before the stirring reaction is 1:1-8.

[0018] The stirring reaction time in step (2) is 10-48 hours.

[0019] In step (3), the dosage ratio of ZIF-67@ZIF-8 to solvent is 0.05-0.4 g: 20-100 mL.

[0020] The usage ratio of the 2-methylimidazole to the solvent in step (3) is 1-10 g: 20-100 mL.

[0021] The mass concentration of the hexadecyltrimethylammonium bromide solution in step (3) is 1-10wt%.

[0022] In step (3), the dosage ratio of ZIF-67@ZIF-8, 2-methylimidazole, hexadecyltrimethylammonium bromide solution and tetraethyl silicate is 0.05-0.4 g: 1-10 g: 1-4 mL: 0.1-1.2 mL.

[0023] The stirring reaction in step (3) is carried out at room temperature and for 30-60 min.

[0024] In step (4), the dosage ratio of ZIF-67@ZIF-8@SiO2, thioacetamide and solvent is 10-100 mg: 10-100 mg: 20-80 mL.

[0025] The temperature of the sulfurization reaction in step (4) is 100-150°C and the time is 1-10 h.

[0026] The inert atmosphere in step (4) is at least one of argon and nitrogen.

[0027] The calcination temperature in step (4) is 400-600°C, the calcination time is 0.5-10h, and the heating rate is 1-20°C / min.

[0028] The solvent used in steps (1) to (4) is at least one of water, methanol and N,N-dimethylformamide (DMF).

[0029] After the separation in steps (1) to (4), the obtained solid product is washed.

[0030] The drying in steps (1) to (4) includes at least one of freeze drying and vacuum drying; the drying temperature is 50-120° C., and the drying time is 1-48 hours.

[0031] The Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst prepared by the above method.

[0032] The above Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst is used as an OER catalyst in the field of hydrogen production by water electrolysis.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The preparation method of the Co9S8 / ZnS / CN@SiO2 catalyst provided by the present invention adopts a step-by-step synthesis process, which can accurately control the components, morphology and spatial distribution, thereby optimizing the structural performance of the catalyst. The method does not require precious metals, has a simple process, low cost, and is conducive to large-scale production and application.

[0034] (2) The catalyst provided by the present invention, wherein the construction of the Co9S8 / ZnS heterojunction forms an interface with strong electronic coupling, promotes charge transfer, and significantly improves the OER catalytic activity. Carbon and nitrogen have good electrical conductivity, which further accelerates charge transfer, reduces resistance loss, and thus enhances electrochemical performance.

[0035] (3) The catalyst provided by the present invention adopts a yolk-shell structure design to significantly increase the specific surface area of ​​the catalyst and the contact area with the electrolyte, thereby improving the reaction rate of OER. The outer SiO2 shell not only provides chemical stability and mechanical strength, but also protects the internal active substances from corrosion by the electrolytic environment, thereby extending the service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope image (SEM) of ZIF-67@ZIF-8@SiO2 obtained in Example 1.

[0037] Figure 2 The scanning electron microscope image (a) and the transmission electron microscope image (b) of Co9S8 / ZnS / CN@SiO2-400 obtained in Example 1.

[0038] Figure 3 This is the X-ray diffraction (XRD) pattern of Co9S8 / ZnS / CN@SiO2-400 obtained in Example 1.

[0039] Figure 4 The catalytic performance test results of the catalysts obtained in Example 1 and Comparative Examples 1-3 are shown in FIG. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0041] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0042] Example 1 (1) Preparation of ZIF-67 1.09 g of Co(NO3)2·6H2O and 1.232 g of 2-methylimidazole were dissolved in 30 mL of methanol. The two solutions were then mixed under stirring and allowed to react for 24 h. After the reaction was completed, the solid product was separated by centrifugation, washed with methanol several times, and dried in an oven at 80 °C for 10 h to obtain ZIF-67 crystals.

[0043] (2) Preparation of ZIF-67@ZIF-8 Disperse 100 mg of ZIF-67 in 30 mL of methanol solution and add 5 mL of Zn(NO3)2·6H2O methanol solution (concentration 30 mg·mL -1 ), add 10 mL of 2-methylimidazole methanol solution (concentration 30 mg mL) under stirring. -1 After the mixed solution was reacted for 24 h, the product was collected by centrifugation, washed three times with methanol, and dried in an oven at 80 °C for 10 h to obtain ZIF-67@ZIF-8.

[0044] (3) Preparation of ZIF-67@ZIF-8@SiO2 180 mg of ZIF-67@ZIF-8 and 4 g of 2-methylimidazole were dispersed in 60 mL of methanol solution and 60 mL of deionized water, respectively. After mixing the two, 4 mL of 5 wt% hexadecyltrimethylammonium bromide (CTAB) solution was added and stirred for 30 min using a magnetic stirrer. 0.1 mL of tetraethyl silicate (TEOS) was evenly added dropwise under stirring and stirred at room temperature for 1 h. After the reaction was completed, the product was separated by centrifugation, washed three times with deionized water, and dried in an oven at 80 ° C for 5 h to obtain the ZIF-67@ZIF-8@SiO2 composite material.

[0045] (4) Preparation of Co9S8 / ZnS / CN@SiO2-400 40 mg of ZIF-67@ZIF-8@SiO2 and 60 mg of thioacetamide were added to 50 mL of methanol solution, and then transferred to the lining of the reactor after ultrasonic dispersion. The reactor was placed in a forced air drying oven and heated to 120 ° C for 3 hours. After the reaction was completed, the product was separated by centrifugation and washed three times with methanol. After drying in an oven at 80 ° C for 5 hours, the sulfide product was obtained. The powder was then placed in a tubular furnace and heated to 400 ° C at a heating rate of 5 ° C / min for calcination for 2 hours under nitrogen protection. After the reaction was completed, it was cooled to room temperature and the Co9S8 / ZnS / CN@SiO2-400 catalyst was collected.

[0046] The operation process of Co9S8 / ZnS / CN@SiO2-400 prepared in this embodiment as an OER catalyst for electrolysis of water to produce hydrogen is as follows: The catalytic activity was tested using a three-electrode system. The carbon cloth (area 1 cm × 1 cm, loading 1 mg cm) loaded with the Co9S8 / ZnS / CN@SiO2-400 composite electrocatalyst prepared in this example -2 ) was used as the working electrode, platinum sheet was used as the counter electrode, Hg / HgO electrode was used as the reference electrode, and 1 M KOH solution was used as the electrolyte.

[0047] The catalytic performance indicators of the obtained catalyst are: current density is 10mA·cm -2 When , the OER overpotential is 382 mV.

[0048] Example 2 The difference from Example 1 is that the calcination temperature of the pyrolysis reaction in step (4) is adjusted to 500° C., thereby preparing the Co9S8 / ZnS / CN@SiO2-500 catalyst.

[0049] The catalytic performance indicators of the obtained catalyst are: current density is 10mA·cm -2 The OER overpotential is 410 mV.

[0050] Example 3 The difference from Example 1 is that the calcination temperature of the pyrolysis reaction in step (4) is adjusted to 600°C, thereby preparing the Co9S8 / ZnS / CN@SiO2-600 catalyst.

[0051] The catalytic performance indicators of the obtained catalyst are: current density is 10mA·cm -2 When , the OER overpotential is 454 mV.

[0052] Comparative Example 1 The difference from Example 1 is that step (2) is omitted, so the Co9S8 / CN@SiO2 catalyst is finally prepared. The specific steps are as follows: (1) Preparation of ZIF-67 1.09 g of Co(NO3)2·6H2O and 1.232 g of 2-methylimidazole were dissolved in 30 mL of methanol. The two solutions were then mixed under stirring and allowed to react for 24 h. After the reaction was completed, the solid product was separated by centrifugation, washed with methanol several times, and dried in an oven at 80 °C for 10 h to obtain ZIF-67 crystals.

[0053] (2) Preparation of ZIF-67@SiO2 180 mg of ZIF-67 and 4 g of 2-methylimidazole were dispersed in 60 mL of methanol solution and 60 mL of deionized water, respectively. After mixing the two, 4 mL of 5 wt% hexadecyltrimethylammonium bromide (CTAB) solution was added and stirred for 30 min using a magnetic stirrer. 0.1 mL of tetraethyl silicate (TEOS) was evenly added under stirring and stirred at room temperature for 1 h. After the reaction was completed, the product was separated by centrifugation, washed three times with deionized water, and dried in an oven at 80 ° C for 5 h to obtain a ZIF-67@SiO2 composite material.

[0054] (3) Preparation of Co9S8 / CN@SiO2 40 mg of ZIF-67@SiO2 and 60 mg of thioacetamide were added to 50 mL of methanol solution, and then transferred to the lining of the reactor after ultrasonic dispersion. The reactor was placed in a forced air drying oven and heated to 120 ° C for 3 hours. After the reaction was completed, the product was separated by centrifugation and washed three times with methanol. After drying in an oven at 80 ° C for 5 hours, the sulfide product was obtained. The powder was then placed in a tubular furnace and heated to 400 ° C at a heating rate of 5 ° C / min for calcination for 2 hours under nitrogen protection. After the reaction was completed, it was cooled to room temperature and the Co9S8 / CN@SiO2 catalyst was collected.

[0055] The catalytic performance indicators of the obtained catalyst are: current density is 10mA·cm -2 When , the OER overpotential is 434 mV.

[0056] Comparative Example 2 The difference from Example 1 is that ZIF-8 is used as a precursor, so ZnS / CN@SiO2 catalyst is finally prepared. The specific steps are as follows: (1) Preparation of ZIF-8 300 mg of Zn(NO3)2·6H2O and 600 mg of 2-methylimidazole were dissolved in 30 mL of methanol. The two solutions were then mixed under stirring and allowed to react for 24 h. After the reaction was completed, the solid product was separated by centrifugation, washed with methanol several times, and dried in an oven at 80 °C for 10 h to obtain ZIF-8 crystals.

[0057] (2) Preparation of ZIF-8@SiO2 180 mg of ZIF-8 and 4 g of 2-methylimidazole were dispersed in 60 mL of methanol solution and 60 mL of deionized water, respectively. After mixing the two, 4 mL of 5 wt% hexadecyltrimethylammonium bromide (CTAB) solution was added and stirred for 30 min using a magnetic stirrer. 0.1 mL of tetraethyl silicate (TEOS) was evenly added under stirring and stirred at room temperature for 1 h. After the reaction was completed, the product was separated by centrifugation, washed three times with deionized water, and dried in an oven at 80 ° C for 5 h to obtain a ZIF-8@SiO2 composite material.

[0058] (3) Preparation of ZnS / CN@SiO2 40 mg of ZIF-8@SiO2 and 60 mg of thioacetamide were added to 50 mL of methanol solution, and then transferred to the inner lining of the reactor after ultrasonic dispersion. The reactor was placed in a forced air drying oven and heated to 120 ° C for 3 hours. After the reaction was completed, the product was separated by centrifugation and washed three times with methanol. After drying in an oven at 80 ° C for 5 hours, a sulfide product was obtained. The powder was then placed in a tubular furnace and heated to 400 ° C at a heating rate of 5 ° C / min for calcination for 2 hours under nitrogen protection. After the reaction was completed, it was cooled to room temperature and the ZnS / CN@SiO2 catalyst was collected.

[0059] The catalytic performance indicators of the obtained catalyst are: current density is 10mA·cm -2 When , the OER overpotential is 552 mV.

[0060] Comparative Example 3 The difference from Example 1 is that step (3) is omitted, so a Co9S8 / ZnS / CN catalyst with a single-layer hollow structure is finally prepared. The specific steps are as follows: (1) Preparation of ZIF-67 1.09 g of Co(NO3)2·6H2O and 1.232 g of 2-methylimidazole were dissolved in 30 mL of methanol. The two solutions were then mixed under stirring and allowed to react for 24 h. After the reaction was completed, the solid product was separated by centrifugation, washed with methanol several times, and dried in an oven at 80 °C for 10 h to obtain ZIF-67 crystals.

[0061] (2) Preparation of ZIF-67@ZIF-8 Disperse 100 mg of ZIF-67 in 30 mL of methanol solution and add 5 mL of Zn(NO3)2·6H2O methanol solution (concentration 30 mg·mL -1 ), add 10 mL of 2-methylimidazole methanol solution (concentration 30 mg mL) under stirring. -1 After the mixed solution was reacted for 24 h, the product was collected by centrifugation, washed three times with methanol, and dried in an oven at 80 °C for 10 h to obtain ZIF-67@ZIF-8.

[0062] (4) Preparation of Co9S8 / ZnS / CN 40 mg of ZIF-67@ZIF-8 and 60 mg of thioacetamide were added to 50 mL of methanol solution, ultrasonically dispersed and then transferred to the lining of the reactor. The reactor was placed in a forced air drying oven and heated to 120 ° C for 3 hours. After the reaction was completed, the product was separated by centrifugation and washed three times with methanol. After drying in an oven at 80 ° C for 5 hours, a sulfide product was obtained. The powder was then placed in a tubular furnace and heated to 400 ° C at a heating rate of 5 ° C / min for calcination for 2 hours under nitrogen protection. After the reaction was completed, it was cooled to room temperature and the Co9S8 / ZnS / CN catalyst was collected.

[0063] The catalytic performance indicators of the obtained catalyst are: current density is 10mA·cm -2 When , the OER overpotential is 454 mV.

[0064] Analysis of attached pictures: Figure 1 This is a scanning electron microscope (SEM) image of ZIF-67@ZIF-8@SiO2. As can be seen from the image, the material presents a regular dodecahedral morphology and has no irregular small crystal particles. This indicates that the ZIF-67@ZIF-8@SiO2 composite material with a core-shell structure has been successfully synthesized.

[0065] Figure 2 Scanning electron microscopy (a) and transmission electron microscopy (b) images of Co9S8 / ZnS / CN@SiO2-400. Figure 2 The scanning electron micrograph (a) shows that the Co9S8 / ZnS / CN@SiO2-400 catalyst maintains a complete dodecahedral morphology. The transmission electron micrograph (b) clearly shows the hollow Yolk-shell structure of the catalyst, with SiO2 as the outer shell. This structural design verifies the successful synthesis of the catalyst and provides a structural basis for its excellent electrocatalytic performance.

[0066] Figure 3The X-ray diffraction (XRD) spectrum of Co9S8 / ZnS / CN@SiO2-400 is shown. It can be seen from the figure that the diffraction peaks of the material at 29.8°, 31.2°, 39.6°, 47.6°, and 52.1° correspond to the (311), (222), (331), (551), and (440) crystal planes of Co9S8. The diffraction peaks at 29.1°, 48.3°, and 57.4° correspond to the (111), (220), and (311) crystal planes of ZnS. This indicates that a composite structure in which Co9S8 and ZnS crystal phases coexist is formed, which further confirms the composition and structure of the prepared Co9S8 / ZnS / CN@SiO2-400 catalyst.

[0067] Figure 4 The catalytic performance results of the catalysts obtained in Example 1 and Comparative Examples 1-3 are shown in FIG. Figure 4 As shown in the OER reaction test, when the current density reaches 10 mA cm -2 When the overpotentials of Co9S8 / CN@SiO2, ZnS / CN@SiO2, and Co9S8 / ZnS / CN catalytic materials were measured, they were 434 mV, 552 mV, and 454 mV, respectively. In contrast, the overpotential of Co9S8 / ZnS / CN@SiO2-400 catalyst at the same current density was only 382 mV. This indicates that the Co9S8 / ZnS / CN@SiO2-400 catalyst prepared in the present invention has significantly enhanced OER activity.

[0068] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst, characterized in that: The following steps are involved: (1) mixing a cobalt salt solution and a 2-methylimidazole solution, allowing the mixture to react, separating, and drying a solid product to obtain ZIF-67; (2) dispersing ZIF-67 in a solvent, adding a zinc salt solution and a 2-methylimidazole solution, stirring the reaction, separating, and drying the solid product to obtain ZIF-67@ZIF-8; (3) Dispersing ZIF-67@ZIF-8 and 2-methylimidazole in a solvent respectively, mixing the two, adding hexadecyltrimethylammonium bromide solution, adding tetraethyl silicate, stirring the reaction, separating, and drying to obtain ZIF-67@ZIF-8@SiO2; (4) ZIF-67@ZIF-8@SiO2, thioacetamide and solvent are uniformly mixed, subjected to sulfidation reaction, separated and dried to obtain a sulfidation product; the sulfidation product is calcined in an inert atmosphere, cooled and a Co9S8 / ZnS / CN@SiO2 catalyst is obtained.

2. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: The cobalt salt in step (1) is at least one of (CH3COO)2Co·6H2O, Co(NO3)2·6H2O, and CoCl2·6H2O; In step (1), the concentration of the cobalt salt solution is 0.1-0.5 mol / L, and the concentration of the 2-methylimidazole solution is 0.2-4 mol / L; The amounts of the cobalt salt solution and the 2-methylimidazole solution in step (1) are such that the molar ratio of cobalt ions to 2-methylimidazole in the mixed solution is 1:2-8; The temperature of the static reaction in step (1) is room temperature and the time is 10-24 hours.

3. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: The zinc salt in step (2) is at least one of Zn(NO3)2·6H2O, Zn(CH3COO)2·2H2O, and ZnCl2; In step (2), the dosage ratio of ZIF-67 to solvent is 50-200 mg:10-50 mL; the concentration of zinc salt solution is 20-40 mg / mL; and the concentration of 2-methylimidazole solution is 20-40 mg / mL.

4. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: The mass ratio of ZIF-67 to 2-methylimidazole in step (2) is 50-200:200-2000; The amount of the zinc salt solution and the 2-methylimidazole solution in step (2) is such that the molar ratio of zinc ions to 2-methylimidazole in the mixed solution before the stirring reaction is 1:1-8; The stirring reaction time in step (2) is 10-48 hours.

5. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: In step (3), the ratio of ZIF-67@ZIF-8 to solvent is 0.05-0.4 g: 20-100 mL; In step (3), the ratio of 2-methylimidazole to solvent is 1-10 g: 20-100 mL; The mass concentration of the hexadecyltrimethylammonium bromide solution in step (3) is 1-10wt%.

6. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: In step (3), the amount ratio of ZIF-67@ZIF-8, 2-methylimidazole, hexadecyltrimethylammonium bromide solution and tetraethyl silicate is 0.05-0.4 g: 1-10 g: 1-4 mL: 0.1-1.2 mL; The stirring reaction in step (3) is carried out at room temperature and for 30-60 min.

7. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: In step (4), the ratio of ZIF-67@ZIF-8@SiO2, thioacetamide and solvent is 10-100 mg: 10-100 mg: 20-80 mL; The temperature of the sulfurization reaction in step (4) is 100-150°C and the time is 1-10 h.

8. The method for preparing the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst according to claim 1, characterized in that: The inert atmosphere in step (4) is at least one of argon and nitrogen; The calcination temperature in step (4) is 400-600°C, the calcination time is 0.5-10h, and the heating rate is 1-20°C / min.

9. A Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst prepared by the method according to any one of claims 1 to 8.

10. Application of the Yolk-shell type Co9S8 / ZnS / CN@SiO2 catalyst as claimed in claim 9 as an OER catalyst in the field of hydrogen production by water electrolysis.